Gambaran Pengalaman Kesepian Pada Mahasiswa Sarjana (S1) Rantau - Sembiring, Astha Christie; Bajirani, Made Padma Dewi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Students who relocate far from their families often grapple with the challenges of adjusting to a new environment, which frequently leads to feelings of loneliness. This loneliness, prevalent among students living away from home, can impede personal growth and have detrimental effects on their well-being if left unaddressed. The primary objective of this study is to explore and characterize the experience of loneliness among regional students. Employing a qualitative methodology with a phenomenological approach, individual analysis units were utilized. The study participants comprised three undergraduate students who had relocated for over three years and had encountered loneliness during their migration. Purposive sampling was employed to select participants, and data were gathered through semi-structured interviews. The Interpretative Phenomenological Analysis (IPA) technique was applied for data analysis. The findings of the analysis yielded five main themes: the conceptualization of loneliness, manifestations of loneliness, the impact of loneliness, triggers of loneliness, and coping strategies for loneliness. Each migrating undergraduate student possesses a unique perspective on loneliness. Loneliness manifests in various forms, such as experiencing isolation in their living environment and on-campus. Furthermore, loneliness adversely affects motivation, disrupts sleep patterns, and heightens emotional sensitivity. The study also revealed that loneliness intensifies in the absence of activities and when confronted with the challenges of living away from home. Various coping mechanisms, including social interaction, engaging in activities, journaling, and accepting one's current situation, were employed to mitigate loneliness during migration. The study's implications underscore the importance of educating migrant students about the nature of loneliness and assisting parents in sensitively addressing the phenomenon of loneliness among migrating students.